2019
DOI: 10.1128/jcm.00042-19
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of a Single Strain of Nontoxigenic Corynebacterium diphtheriae bv. Belfanti ( Corynebacterium belfantii ) in Four Patients with Cystic Fibrosis

Abstract: Cystic fibrosis (CF) patients are commonly colonized by bacterial pathogens, which can induce persistent lung inflammation and may contribute to clinical deterioration. Colonization of CF patients and cross-transmission by Corynebacterium diphtheriae have not been reported so far. The aim of this article was to investigate the possibility of a cross-transmission of C. diphtheriae biovar Belfanti between four patients of a CF center. C. diphtheriae biovar Belfanti (now formally called C. belfantii) isolates wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Our study is novel in that it is the first study, to our knowledge, to whole-genome sequence a large collection of C. diphtheriae isolates collected in North America. Previous groups have sequenced collections of C. diphtheriae from Germany, Belarus, South Africa, and Australia (2,7,9,(11)(12)(13)(14)(15). Interestingly, our dominant sequence type, ST76, has only been reported in PubMLST.org, an MLST database, in 9 isolates from Saint Petersburg, Russia, spanning the years 2005 to 2010.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our study is novel in that it is the first study, to our knowledge, to whole-genome sequence a large collection of C. diphtheriae isolates collected in North America. Previous groups have sequenced collections of C. diphtheriae from Germany, Belarus, South Africa, and Australia (2,7,9,(11)(12)(13)(14)(15). Interestingly, our dominant sequence type, ST76, has only been reported in PubMLST.org, an MLST database, in 9 isolates from Saint Petersburg, Russia, spanning the years 2005 to 2010.…”
Section: Discussionmentioning
confidence: 95%
“…WGS also provides the ability to search for virulence factors such as diphtheria toxin and antimicrobial resistance markers. WGS had been used to elucidate transmission dynamics of C. diphtheriae previously (2,7,9,(11)(12)(13)(14)(15) and has shown that unrelated C. diphtheriae genomes differ by approximately 30,000 SNPs or more, whereas epidemiologically linked outbreak isolates differ by up to 150 SNVs (9,12). Similarly, unrelated isolates have been found to be more than 1,000 alleles different when using cgMLST analysis, whereas related isolates have been within 5 alleles (12).…”
mentioning
confidence: 99%
“…In addition, we demonstrate an association between alterations in chromosomally encoded targets and phenotypic resistance for quinolone, trimethoprim, and rifampicin. Fluoroquinolone resistance was previously linked to mutations in the gyrA gene in C. amycolatum [77], C. striatum [78], and C. belfantii [79] but seemingly never for C. diphtheriae. Finally, we demonstrate the co-occurrence within some strains of multiple resistance determinants and uncover a previously undescribed large resistance plasmid in C. diphtheriae.…”
Section: Discussionmentioning
confidence: 99%
“…This genus can work to neutralize acidic conditions that damage teeth [140] and Kingella is acidogenic [141], so their co-occurrence in the CF network may indicate that they complement each other in the acidic CF oral cavity. The association between Corynebacterium and Selenomonas in CF is reasonable, as both have been implicated in CF [142][143][144].…”
Section: Treponema + Dialistermentioning
confidence: 83%